There and Back Again: The Quest and Self-Discovery in J.R.R. Tolkien’s The Hobbit - Arslan, Murat (Journal of History Culture and Art Research, 2015)
‘There and Back Again’: The Quest and Self-Discovery in J.R.R. Tolkien’s The Hobbit Abstract J.R.R. Tolkien contributed a lot to English fantasy and children’s literature. In his novel called The Hobbit, he presents the adventure of the hobbit, Bilgo Baggins and thirteen dwarves who crave for getting their homeland back. Throughout their journey, they experience many dangerous situations. However, it is observed that the novel can be considered as a Bildungsroman. The main character, Bilbo Baggins has his own self-discovery through this journey. At the beginning of the novel, he is a domestic character who hesitates to show courage and gets afraid easily. Later, he not only challenges the outside world but also the inner self whose Baggins side is dominant and prevents him to have an active character. When he is back again in his hobbit-hole, he is not the same person anymore. My paper will be on the main character’s change throughout the novel and examplify his challenge both physically and metaphorically.